Fast Quantitative Determination of Principal Phenolic Anti-oxidants in Rosemary Using Ultrasound-Assisted Extraction and Chemometrics-Enhanced HPLC–DAD Method - Xie, Lixia; Li, Zhineng; Li, Haitao; Sun, Jiayu; Liu, Xueying; Tang, Jianxin; Lin, Xizhu; Xu, Laijun; Zhu, Yuefang; Liu, Zhi; Wang, Tong (Food analytical methods, 2023)
Rosemary is an essential source of natural antioxidants, and its extracts have been practised as a preserving agent in foods. A simple, fast, and efficient quantitative determination of principal phenolic antioxidants in rosemary with efficient sample preparation is of great importance for evaluating the quality of rosemary scientifically. This paper presented a chemometrics-enhanced high-performance liquid chromatography with photodiode-array detector (HPLC–DAD) method for simultaneous determination of rosmarinic acid (RA), carnosol (CAR), and carnosic acid (CA) in ultrasound-assisted rosemary extracts. After ultrasound-assisted extraction, the chromatographic procedure in less than 10 min performed with UV detection in the range of 200–390 nm. The alternating trilinear decomposition algorithm in second-order calibration has been applied in extracting relevant qualitative and quantitative information from the three-dimensional chromatographic data. The correlations between the recovered spectra and their normalized pure spectra for RA, CAR, and CA were 0.9906, 0.9988, and 0.9998, respectively. The average recoveries for RA, CAR, and CA were 94.1 ± 3.1%, 92.1 ± 4.1% and 91.8 ± 4.9%, respectively. Due to the second-order advantage, satisfactory resolution and acceptable quantification results were obtained in the presence of overlapping peaks. It expected that this study can provide some valuable references for the simultaneous determination of principal phenolic antioxidants in the quality control of rosemary. Graphical Abstract